Nurturing dialogue among cultures through stories: pedagogical reflections - Viviana La Rosa (University of Bologna, 2020)
Making up and consuming stories is not only a human imperative, as Jonathan Gottschall affirms, but a real formative condition for each people. First of all, indeed, the sheer understanding of stories is a human experience of relationality, as well as a necessary and privileged opportunity for full human formation. In line with these premises, this contribution intends to stimulate reflection on reading and narration, starting from early childhood. In this sense, the narration is an elective opportunities that allow children to think of themselves as «cultural beings» in the relationship. In other words, this pedagogical reflection defines children as beings capable of dialogue and intercultural understanding, and explores the ability of reading, individual and shared, to encourage the development of empathic and relational skills. Finally, this work explores the action of narrating as a key experience for the acquisition of intercultural skills and the promotion of inclusive processes, analyzing the most recent pedagogical studies, as well as the contributions of cognitive criticism and neuroscience.